Implementasi Pembelajaran Ṭaharah Dalam Perspektif Kitab Safīnah An-Najāh Di Smp Pelita Al-Qur’an Krasak Wonosobo - Fakhira Zulfia; Muchottob Hhamzah; Muhammad Yusuf Amin Nnugroho (Student Scientific Creativity Journal, 2024)
. This study aims to determine the implementation of taharah learning at Pelita Al-Qur'an Junior High School Krasak Wonosobo by paying attention to the development of students' behavior before and after learning. This type of research is qualitative research, with field research methods. The subjects in this study were 7th grade students of Pelita Al-Qur'an Junior High School Krasak Wonosobo. The samples taken were students in grades 7A, 7B, and 7C. Data collection using observation, interviews, and documentation. Implementation of Taharah Learning is learning about the procedures for purification, removing impurities, purifying oneself from hadats. The research that has been done concludes that there is a change between students who have never learned about taharah and those who have learned taharah. The learning that is done also seems fun because there is practice in every material. It's just that the media and facilities available are inadequate so that children cannot understand optimally.